What are children for? : on ambivalence and choice - Berg, Anastasia; Wiseman, Rachel (Journalist) (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2024)
"A modern argument, grounded in philosophy and cultural criticism, about childbearing ambivalence and how to overcome it. Becoming a parent, once the expected outcome of adulthood, is increasingly viewed as a potential threat to the most basic goals and aspirations of modern life. We seek self-fulfillment; we want to liberate women to find meaning and self-worth outside the home; and we wish to protect the planet from the ravages of climate change. Weighing the pros and cons of having children, Millennials and Zoomers are finding it increasingly difficult to judge in its favor. With lucid argument and passionate prose, Anastasia Berg and Rachel Wiseman offer the guidance necessary to move beyond uncertainty. The decision whether or not to have children, they argue, is not just a women's issue but a basic human one. And at a time when climate change worries threaten the very legitimacy of human reproduction, Berg and Wiseman conclude that neither our personal nor collective failures ought to prevent us from embracing the fundamental goodness of human life--not only in the present but, in choosing to have children, in the future"--